Oral contraceptive consumption and cerebral venous sinuses thrombosis - Kukum, Jha Gupta; Rajiv, Jha (Journal of Society of Surgeons of Nepal, 2016)
Introduction: Cerebral venous sinus thrombosis (CVST) is a rare cause of stroke and the clinical presentation is variable. One of the more common acquired risk factors of venous sinus thrombosis is oral contraceptive medications. While the prognosis for CVST is favorable, it is important to identify and treat early to prevent neurologic deficits. CVST accounts for 0.5% of strokes and most commonly presents with headaches and in many cases focal neurologic deficits. Diagnosis is confirmed with neuroimaging including CT angiography or MR angiography. Treatment consists of anticoagulation and in some cases, thrombolytic therapy is beneficial. The overall prognosis of CVST is favorable. The objective of the study is to describe the features of a series of patient with CVST due to consumption of OCPs, treated in the department of Neurosurgery, Bir hospital and OM hospital, and to discuss the risk factors associated with consumption of OCPs, its presentation, and outcome. Methods: This is a retrospective case series carried out in the department of Neurosurgery, Bir hospital and OM hospital during the year September 2012 to September 2014. Demographic features like age, presenting symptoms, clinical findings and outcome were analyzed. All cases received heparin or LMWH followed by Warfarin. Results: Nine patients were identified over a period of 2 years. The presenting symptoms included headache, vomiting, loss of consciousness, focal neurological deficit, seizure and neck pain. Signs found included papilloedema, fever, slurring of speech and focal neurological signs. Conclusion: Dural sinus thrombosis is a rare and under-recognized cause of headache that should be considered in women with recent introduction of hormonal contraception. The absence of papilledema and a negative CT brain should not halt further workup. MRI/venogram is mandatory to confirm the diagnosis. Journal of Society of Surgeons of Nepal Vol.17(1) 2014: 2-5